EFEKTIVITAS PENERAPAN DISCHARGE PLANNING TERHADAP KESIAPAN PULANG DAN KEPUASAN PASIEN CONGESTIVE HEARTH FAILURE (CHF) DI MURNI TEGUH MEMORIAL HOSPITAL - Sagala, Lam Murni Br.; Hasibuan, Muhammad Taufik Daniel (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Congestive Hearth Failure (CHF) is one of the biggest contributors to death in the world. The recurrence of recurrence after hospitalization in CHF patients increases every year due to lack of knowledge of the disease, treatment to be undertaken and care after returning from health services. One effort that can be done in reducing the recurrence rate in patients with CHF yaiyu is by planning treatment activities that will be undertaken by patients starting from thebeginning of entering health services until planning to go home.Discharge Planning is a process that starts when a patient enters health services to return home from health services so that patients get continuous health care both in the healing process and in maintaining their health status until the patient feels ready to return to his environment and is satisfied with treatment that has been undertaken in health services. The purpose of this study was to determine the effectiveness of the application of discharge planning to the readiness of returning home and patient satisfaction of Congestive Heart Failure (CHF) patients at Murni Teguh Memorial Hospital. The research method that will be used in this study is Quasi Experiment (quasi-experimental) post test only non equivalent control group, where in this design there are no restrictions on randomization when entering subjects into the treatment group or the control group. The sample in this study were 90 respondents (45 treatment group respondents and 45 control group respondents). The sampling technique in this study with non probability techniques with consecutive sampling approach. Bivariate analysis is performed to test hypotheses or to determine the effectiveness of the relevant variables used are non-parametric statistics with the type of test mann withney t-test. The results of the study are significant if the p value is less than 0.05 (p value <0.05). The results of this study indicate that the application of discharge planning is effective in increasing the readiness and satisfaction of CHF patients.